Why do victims matter?. Issue 1 (12th January 2022) - Moritz, Joshua M.
Abstract: Why do victims matter? While many today take for granted the idea that victims have moral value, the historical route that got us here is not so broadly known. The short answer is that Jesus of Nazareth and his transformation of the meaning of suffering is the ultimate reason why victims matter.